The basics of construction of jet-drop optical systems for measuring electric field strength. Parth 2 - E. V. Leun (Омский научный вестник)
In this part of the article, the discussion of the construction of jet-drop optical measuring systems (JDOMS) for monitoring the electric field strength continues. The possibilities of increasing the resolution are considered. A variant of the interference JDOMS using triangulation stroboscopic measurements of displacements of charged moving droplets using a pulsed acousto-optic interferometer of transverse displacements of a laser beam is presented. The possibilities of increasing the charge/mass ratio of charged droplets, the features of using liquid metals and their two- and three-component alloys as liquids, the use of inhomogeneous droplets in the form of hollow, hollow microspheres similar to soap bubbles and/or based on a porous (dispersed) material are discussed.